2021
DOI: 10.1111/odi.13862
|View full text |Cite
|
Sign up to set email alerts
|

The presence of Prevotella melaninogenica within tissue and preliminary study on its role in the pathogenesis of oral lichen planus

Abstract: Objective Oral lichen planus (OLP) is a chronic inflammatory disease that occurs in the oral mucosa with characteristic white striations lesions, recurrent erosions, and pains. The etiology and pathogenesis of OLP are still unclear. Materials and Methods We analyzed the bacterial community structure of buccal mucosa in patients with OLP and normal controls by high‐throughput sequencing. Fluorescence in situ hybridization (FISH) was used to detect Prevotella melaninogenica (P. melaninogenica) in 13 OLP samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
0
10
1
Order By: Relevance
“…Contrary to our findings, Robayo and coworkers did not detect P. melaninogenica in oropharyngeal carcinoma tissue samples [39], but de Martin et al confirmed its presence in the tonsillar OSCC [40]. A recent study by Zheng et al using in situ hybridization established the presence of P. melaninogenica in oral lichen planus [41].…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our findings, Robayo and coworkers did not detect P. melaninogenica in oropharyngeal carcinoma tissue samples [39], but de Martin et al confirmed its presence in the tonsillar OSCC [40]. A recent study by Zheng et al using in situ hybridization established the presence of P. melaninogenica in oral lichen planus [41].…”
Section: Discussioncontrasting
confidence: 99%
“…Oral lichen planus (OLP) is characterized as a chronic inflammatory condition affecting the oral mucosa with white striated, non-erosive or erosive lesions. In 13 OLP cases, the abundance of P. melaninogenica was significantly higher in comparison to samples from healthy mucosa [ 164 ]. Based on FISH analyses, epithelial and lamina propria invasion by P. melaninogenica was observed in OLP samples.…”
Section: Prevotella Involvement In Oral Conditions Of Clinic...mentioning
confidence: 99%
“…Based on FISH analyses, epithelial and lamina propria invasion by P. melaninogenica was observed in OLP samples. As a novel aspect, P. melaninogenica was confirmed to activate the NF-kB signaling pathway after adhering to and invading macrophages, thus, indicating its role in the pathogenesis of OLP [ 164 ]. In recurrent aphthous stomatitis, Prevotella and Alloprevotella seem to be among the 10 most abundant genera, and the formation of aphthous ulcers may be due to the colonization of Escherichia coli and/or Alloprevotella [ 165 ].…”
Section: Prevotella Involvement In Oral Conditions Of Clinic...mentioning
confidence: 99%
“…Infection and Drug Resistance 2023:16 690 infections 28 and oral lichen planus. 29 For another, of the 106 enrolled patients, Tropheryma whipplei was the sole pathogen isolated in 4 patients, comprising 15,428, 4311, 95 and 88 reads respectively, but the symptoms of only 2 patients were consistent with the final clinical diagnosis, the remaining two patients were regarded as positive depending on the criteria for a positive mNGS result but presented discordant clinical signs and symptoms. Tropheryma whipplei is a bacterium associated with Whipple's disease, which commonly demonstrates as weight loss, arthralgia, diarrhea and is diagnosed by the histology of small bowel biopsies.…”
Section: Dovepressmentioning
confidence: 99%